PERSONNEL MANAGEMENT BASED ON THE SAPPURISADHAMMA 7 FOR MEDIUM SCHOOL ADMINISTRATORS UNDER THE OFFICE OF NAKHON RATCHASIMA PRIMARY EDUCATIONAL SERVICE AREA 6 - Panyakmo (Dokmai), PhraPrapas (Journal of Graduate MCU KhonKaen Campus, 2020)
The objectives of this research were: 1) to study the current state of personnel administration for medium school administrators under the Office of Nakhon Ratchasima Primary Educational Service Area 6; 2) to study personnel administration for school administrators in medium schools according to the principle of the seven Sappurisa Dhammas (sappurisa-dhamma, qualities of a good man), under the Office of Nakhon Ratchasima Primary Educational Service Area 6; 3) to propose the guideline for promoting the personnel administration for school administrators in medium schools according to the principle of the seven Sappurisa Dhammas, under the Office of Nakhon Ratchasima Primary Educational Service Area 6. The research results were as follows: The personnel management according to the seven Sappurisa Dhammas for medium school administrators under the Office of Nakhon Ratchasima Primary Educational Service Area 6, in general is rated at a high level (mean = 4.23) based on the samples’ opinions. In descending order, the highest was to enhance the efficiency of the civil service practice, recruitment and appointment (least, mean = 4.19). A comparison of opinions of administrators and teachers towards the overall showed indifference. Classified according to the level of education, differences were found with statistical significance at .05 and other areas were significantly different at .01. The suggestions for promoting personnel administration according are that according to the opinions of administrators and teachers, there should be a survey of the development needs of teachers and educational personnel; administrators should support teachers and personnel to be developed, such as participating in training and academic seminars in order to constantly develop their potential; educational institutions should have fair procedures for recruitment, placement or appointment of personnel.